‘Valorisation’. For a renewed vitality of the monuments - Giovanni Carbonara (Agathón)
After an introduction comparing the concepts of ‘restoration’ and ‘valorisation’, we go on to examine the limits of modern restoration, in a critical and conservative sense. It is characterised by its methodological openness towards modernity, on the one hand, and thematic openness on the other, relating to a broader category of ‘assets’ than the traditional one, not reserved only for expressions of high historical and artistic value. It then goes on to consider what, although it concerns the world of pre-existence, cannot be defined as restoration and preservation; finally, it considers the methods and tasks of enhancement, which, in its most authentic sense, goes hand in hand with restoration and in some respects follows it, guaranteeing first the conditions for recognition of the asset to be protected, then those of its good management, use and maintenance over time.